Analisis Swot Usaha Mikro, Kecil Dan Menengah (UMKM) Pada Mie Ayam Petronas Cabang Pasir Gombong - Fitria Noviantika; Daspar, Daspar (CV. ITTC INDONESIA, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are business activities that have the potential to expand the business sector and economy by providing extensive employment opportunities for the community.(Absari et al., 2023) The purpose of this study is to determine the challenges associated with using SWOT analysis as a method to improve competitiveness. Imminent risks can be controlled and future opportunities enhanced through strategic management. (Musnaeni et al., 2022) This article explains how to determine the TOWS Matrix including SO strategy, WO strategy, ST strategy, and WT strategy or SWOT Strength, Weakness, Opportunity, Threat Matrix. Case studies such as in micro, small and medium enterprises (MSMEs) case study on Petronas Chicken Noodle pasir gombong branch. This research uses a literature study methodology, examining a range of scholarly sources pertinent to the subject matter. It is anticipated that the findings of this study will contribute both theoretically and practically to the analysis of business development through the use of strategic management science.